An Alliance Of Women : Immigration And The Politics Of Race - Merrill, Heather (Book collections on Project MUSE., 2006)
Heather Merrill investigates how migrants and Northern Italians struggle over meanings and negotiate social and cultural identities. Using rich ethnographic material, Merrill traces the emergence of Alma Materan anti-racist organization formed to address problems encountered by migrant women. Through this analysis, she reveals the dynamics of an alliance consisting of women from many countries of origin and religious and class backgrounds.